A new semi-subterranean diving beetle of the Hydroporus normandi-complex from south-eastern France, with notes on other taxa of the complex (Coleoptera: Dytiscidae) - Manuel, Michael (Zootaxa, 2013)
Hydroporus galloprovincialis sp. n. is described from Jouques, north-east of Aix-en-Provence in south-eastern France (Provence). The new species belongs to the Hydroporus memnonius-group, within which it is the only ascertained nor-mandi-complex species of the French fauna. The habitat (small springs) and morphological features of the species suggest a semi-subterranean life style. It can be separated from the other species of the complex notably by its more elongated and parallel-sided habitus, by its wider pronotum and flatter dorsal surface, and furthermore differs from H. normandi Régim-bart, 1903 by a different shape of the gonocoxa. Illustrations are provided for other described normandi-complex species and subspecies for comparison. Analyses of partial cox1 sequences indicate that the three sampled H. normandi-complex species (H. galloprovincialis sp. n., H. normandi and H. lluci Fery, 1999) diverged recently; their relationships are unre-solved. H. galloprovincialis sp. n. is for the moment the only species of the genus Hydroporus Clairville, 1806 endemic to continental France.